2015
DOI: 10.3390/ijerph120809036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Anemia and Iron Deficiency in Kuwait

Abstract: The objective of this study was to assess the prevalence of anemia and iron deficiency (ID) of a nationally representative sample of the Kuwait population. We also determined if anemia differed by socioeconomic status or by RBC folate and vitamins A and B12 levels. The subjects who were made up of 1830 males and females between the ages of 2 months to 86 years, were divided into the following age groups (0–5, 5–11, 12–14, 15–19, 20–49, ≥50 years). Results showed that the prevalence of anemia was 3% in adult ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 20 publications
3
27
0
3
Order By: Relevance
“…Another significant finding in our study was the very high prevalence of anaemia (30%) in Kuwaiti pregnant women. Several studies have shown that anaemia is a significant public health problem in Kuwait (23)(24)(25). Previous studies from Kuwait reported that 28.7-36.8% of pregnant Kuwaiti women were anaemic (25,26) and our results agree with these reports.…”
Section: Discussionsupporting
confidence: 83%
“…Another significant finding in our study was the very high prevalence of anaemia (30%) in Kuwaiti pregnant women. Several studies have shown that anaemia is a significant public health problem in Kuwait (23)(24)(25). Previous studies from Kuwait reported that 28.7-36.8% of pregnant Kuwaiti women were anaemic (25,26) and our results agree with these reports.…”
Section: Discussionsupporting
confidence: 83%
“…These estimates are far higher than our estimate in this study. However, a fairly recent study has estimated the prevalence of anemia in adolescents (12-14 years) to be 8.8% in males and 5.7% in females 15 . Over many years KNSS has used capillary blood that is collected from finger, measuring Hb by the portable HemoCue method.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies (1) have been conducted to investigate the epidemiology of IDA. Most of them were focused on populations of developing countries (15)(16)(17)(18), selected cohorts of patients with kidney (19) and/or cardiovascular diseases (20).…”
mentioning
confidence: 99%